Determinants of workplace injury among Thai Cohort Study participants. Issue 7 (17th July 2013) - Berecki-Gisolf, Janneke; Tawatsupa, Benjawan; McClure, Roderick; Seubsman, Sam-ang; Sleigh, Adrian
Abstract : Objectives: To explore individual determinants of workplace injury among Thai workers. Design: Cross-sectional analysis of a large national cohort. Setting: Thailand. Participants: Thai Cohort Study participants who responded to the 2009 follow-up survey were included if they reported doing paid work or being self-employed (n=51 751). Outcome measures: Self-reported injury incidence over the past 12 months was calculated. Multivariate logistic regression models were used to test associations between individual determinants and self-reported workplace injury. Results: Workplace injuries were reported by 1317 study participants (2.5%); the incidence was 34 (95% CI 32 to 36)/1000 worker-years for men, and 18 (17–20) for women. Among men working ≥41 h and earning <10 000 Baht, the injury rate was four times higher compared with men working <11 h and earning ≥20 001 Baht; differences in injury rates were less pronounced in women. Multivariate modelling showed that working ≥49 h/week (23%) and working for ≤10 000 Bath/month (37%) were associated with workplace injury. The increase in injury risk with increased working hours did not exceed the risk expected from increased exposure. Conclusions: Reductions in occupational injury rates could be achieved by limiting working hours to 48/week. Particularly for Thai low wage earners and those with longer workdays, there is a need for effective injury preventive programmes.